2023
DOI: 10.1177/00469580231152071
|View full text |Cite
|
Sign up to set email alerts
|

Insights Into the Relationships Between Health Communication and Doctor-patient Relationship: A Scientometric Analysis Based on CiteSpace and Validation of Questionnaires

Abstract: In order to understand the research status of the relationship between health communication and doctor-patient relationship, and to explore a new path of the impact of health communication on doctor-patient relationship, this paper adopted qualitative methods to quantize the literature over the past 10 years in the Web of Science database and carried out Co-Authorship Analysis, Co-Citation Analysis and Co-Occurrence Analysis based on CiteSpace. In addition, according to the results of bibliometric research, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…At the same time, the treatment process is accompanied by a number of psychological phenomena that are related to the personal characteristics of the patient, the doctor, and the treatment methods chosen by him/her. Modern research indicates that, for the most part, psychological interaction between a doctor and a patient occurs spontaneously, and their communication depends on a specific situation where there is a possibility of a lack of contact (trust) between them (Wang et al, 2022;Lu et al, 2023;Wang et al, 2023). This has a negative impact on the information content of the patient's medical history and the outcome of treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the treatment process is accompanied by a number of psychological phenomena that are related to the personal characteristics of the patient, the doctor, and the treatment methods chosen by him/her. Modern research indicates that, for the most part, psychological interaction between a doctor and a patient occurs spontaneously, and their communication depends on a specific situation where there is a possibility of a lack of contact (trust) between them (Wang et al, 2022;Lu et al, 2023;Wang et al, 2023). This has a negative impact on the information content of the patient's medical history and the outcome of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Communicative tolerance is an important component of a medical professional's professional competence. The ability to establish a trusting relationship with patients allows the doctor to build an effective treatment strategy and ensure mutual understanding during this process (Lu et al, 2023). A sign of psychological contact with the patient is that the Source: compiled by the authors patient will not doubt the correctness of the diagnostic and treatment tactics and will follow the doctor's prescriptions.…”
Section: Discussionmentioning
confidence: 99%
“…The sudden increase in global scholarly interest in a particular area is bound to be a common problem. [41] For example, the outbreak of COVID-19 in late 2019 to early 2020. Globally, the countries at the forefront of research on risk management in the DPR are the United States and the United Kingdom, with both fruitful research results and a relatively high total and average number of citations per article.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of burst words reveals keywords that change rapidly or increase dramatically in number in a short period of time, allowing the emergence of research hotspots and frontiers at different times, and is a key indicator of hotspots and emerging trends in the research field. [41,42] To better understand the temporal trends of the study topics, we used CiteSpace to analyze the topic burst keywords, as shown in Figure 5. The first 15 bursts of keywords were selected, and all keywords had an intensity of more than 4.…”
Section: Trend Analysis Of Theme Evolutionmentioning
confidence: 99%